The net effects of medical malpractice tort reform on health insurance losses: The Texas experience - Patricia Born; J. Bradley Karl; W. Kip Viscusi (Health Economics Review, 2017)
In this paper, we examine the influence of medical malpractice tort reform on the level of private health insurance company losses incurred. We employ a natural experiment framework centered on a series of tort reform measures enacted in Texas in 2003 that drastically altered the medical malpractice environment in the state. The results of a difference-in-differences analysis using a variety of comparison states, as well as a difference-in-difference-in-differences analysis, indicate that ameliorating medical malpractice risk has little effect on health insurance losses incurred by private health insurers.
Keywords: K13; I10; G22; 330; Medical malpractice; Health insurance; Tort reform; Liability